Two-Dimensional Preoperative Digital Templating is Less Accurate When Using a Collared Triple Taper Stem Versus a Single Taper Design - Claudio Diaz-Ledezma, MD; Angel X. Xiao, MD, MSE; Juan David Lizcano, MD; Erik N. Hansen, MD; Camilo Restrepo, MD; William J. Hozack, MD (Arthroplasty Today)
Background: Collared triple taper stems (CTTS) and single taper stems (STS) have an excellent performance in primary total hip arthroplasty (THA). While 2-dimensional radiographic templating is accurate for STS, data are lacking for CTTS. We hypothesize that CTTS’ more anatomical design in the anteroposterior dimension may lead to inaccurate templating sizing. This study compared templating accuracy of CTTS to a predecessor STS in THA patients. Methods: 106 THA performed with CTTS were compared to 106 THA performed with STS by 2 high-volume surgeons. The stems chosen for comparison were manufactured by the same company, use the same templating software, shared an identical medial-lateral profile, and offered the same size range. The ability of digital templating to predict final implant size was evaluated. Results: Template to stem accuracy was 36.8% for CTTS and 49.1% for STS (P = .07). Accuracy within 1 size was 88.7% for CTTS versus 95.2% for STS (P = .1). CTTS was implanted using a smaller size compared to the template twice as frequently as STS (43.4% vs 20.8%; P < .01). CTTS was 3.7 times more likely to have implants 2 or more sizes under the template compared to STS (10.4% vs 2.8%; P = .02). In logistic regression, the only predictor of implant 2+ sizes under the template was type of stem (P = .04). Conclusions: The accuracy of conventional templating for CTTS is lower than the predecessor STS, with the template often suggesting a larger size. Bi-planar or 3-dimensional preoperative templating could potentially be a more accurate technique, especially during the initial learning curve with these stems.